Effect of PRE and POST-Directed Herbicides for Season-Long Nutsedge (Cyperus spp.) Control in Bell Pepper. (September 2014) - Miller, M. Ryan; Dittmar, Peter J.
Abstract : Fomesafen and imazosulfuron are two recently registered herbicides for use in Florida bell pepper. Field studies were conducted in 2012 and 2013 to evaluate PRE, POST-directed (POST-DIR), and PRE followed by (fb) POST-DIR control programs utilizing these new herbicides for nutsedge control in Florida bell pepper. PRE treatments included: S -metolachlor at 0.71 and 1.07 kg ai ha −1, fomesafen at 0.28 and 0.42 kg ai ha −1, S -metolachlor at 0.71 kg ha −1 + fomesafen 0.28 kg ha −1, and S -metolachlor at 1.07 kg ha −1 + fomesafen at 0.42 kg ha −1 . POST-DIR treatments included imazosulfuron at 0.21 and 0.34 kg ai ha −1 . PRE fb POST-DIR treatments included S -metolachlor at 0.71 or 1.07 kg ha −1 fb imazosulfuron at 0.21 kg ha −1 and fomesafen at 0.28 or 0.42 kg ha −1 fb imazosulfuron at 0.21 kg ha −1 . Nutsedge control in both years at 28 d after planting was similar among all PRE treatments providing ≤ 60% control. The addition of imazosulfuron POST-DIR following S -metolachlor or fomesafen PRE provided greater control compared to S -metolachlor or fomesafen alone 14, 21, and 28 d after the POST-DIR application. Plots treated with S -metolachlor resulted in lower marketable weight and marketable fruit count compared to fomesafen in 2012; however, this was not observed in 2013. The results for these studies indicate the importance of a PRE fb POST-DIR herbicide for nutsedge control and that fomesafen or S -metolachlor PRE fb imazosulfuron POST-DIR provides growers with a viable tool capable of achieving season-long control of nutsedge in bell pepper.